PREMARITAL CHECK-UP DALAM PANDANGAN KEPALA KUA SEMAMPIR KOTA SURABAYA - Panjalu, Gandhung Fajar (Muhammadiyah University of Surabaya, 2022)
Premarital health tests are a series of tests that couples must undergo before getting married. The procedures for carrying out pre-marital health checks in Surabaya were determined in 2017 according to a circular issued by the Mayor of Surabaya, Tri Rismaharini. This research aims to explore pre-marital health examinations in the KUA Semampir sub-district, Surabaya city, and how the KUA responds to the results of these pre-marital health tests. This research is field research. The results of this research show that (1) KUA does not have a maximum limit on when the test must be carried out. (2) The health test examination is carried out at the health center. (3) The prospective bride and groom will also receive reproductive counseling. (4) If the results of the test show that the prospective bride and groom are unhealthy, the KUA has no right to postpone the marriage. The decision is completely left to the bride and groom.